The effects of a global postural exercise program on temporomandibular disorder - Alexandre Fiorelli; Eduardo Aguilar Arca; Carolina Menezes Fiorelli; Alitéia Aparecida Souza Rodrigues; Ana Carla Furcin; Alberto De Vitta; Cesar Becalel Waisberg; Débora de Melo Trize; Paulo Henrique Weckwerth
Abstract Changes in the suboccipital muscles and the hamstrings may interfere with head posture and the biomechanics of the temporomandibular joint, both of which contribute to the severity of temporomandibular disorders (TMD). The objective of this investigation was to evaluate the effects of a global postural exercise program (GPEP) on pain intensity and mouth-opening range of motion (ROM) in women with TMD. The participants were comprised of 30 women with TMD who were divided into two groups: an experimental group (EG) and a control group (CG). A pressure algometer was used for pain assessment and a paquimeter was used to measure ROM. The duration of the GPEP was six weeks. In the EG, there was a reduction in pain intensity and an increase in mouth-opening ROM compared to the CG. Therefore, we concluded that the GPEP was effective in relieving pain in all of the evaluated muscles and regions, and in increasing mouth-opening ROM in women with TMD.